Effects of H2SO4, GA3, and cold stratification on the water content, coat composition, and dormancy release of Tilia miqueliana seeds - Wu, Yu; Huang, Wen Hui; Peng, Chen Yin; Shen, Yong Bao; Visscher, Anne M.; Pritchard, Hugh W.; Gao, Qiu; Sun, Xiao Rui; Wang, Ming Zhu; Deng, Zhiyun (Frontiers in Plant Science, 2023)
Introduction Tilia miqueliana is an endemic species whose population is declining. The permeability barrier and mechanical constraint of the pericarp (seed coat) are important causes of its seed dormancy. Although there has been considerable research on this subject, questions remain regarding how the permeability barrier and mechanical constraint of the seed coat are eliminated during dormancy release and how water enters the seed. Therefore, protecting the species by improving its germination/dormancy breaking in the laboratory is urgent Methods In this study, the changes in the cellular structure, mechanical properties, and components of the Tilia miqueliana seed coat after an H2SO4-gibberellic acid (GA3) treatment were analyzed during dormancy release. Various analyses (e.g., magnetic resonance imaging, scanning electron microscopy, and paraffin section detection) revealed the water gap and water channel. Results The H2SO4 treatment eliminated the blockage at the micropyle and hilum of the seeds. Water entered the seeds through the water gap (micropyle) rather than through the hilum or seed coat, after which it dispersed along the radicle, hypocotyl, and cotyledon to the endosperm. During the cold stratification period, the cellular structure was damaged and an increasing number of holes appeared on the inner and outer surfaces of the seed coat. Vickers hardness tests showed that GA3 decreased the seed coat hardness. Additionally, the seed coat lignin and total phenol contents continuously decreased during the cold stratification period. Notably, the Liquid chromatography–mass spectrometry (LC–MS) analysis of the seed coat detected polyethylene glycol (osmoregulator), which may have destabilized the water potential balance inside and outside the seed and increased the water content to levels required for germination, ultimately accelerating seed dormancy release. Discussion This sophisticated and multi-level study reveals how H2SO4 and GA3 eliminate the permeability barrier and mechanical constraints of the seed coat during dormancy release of Tilia miqueliana seeds. This will be beneficial to artificially assist the natural regeneration and population expansion of Tilia miqueliana.